2012
DOI: 10.1017/s0007114512000980
|View full text |Cite
|
Sign up to set email alerts
|

A novel soluble β-1,3-d-glucan Salecan reduces adiposity and improves glucose tolerance in high-fat diet-fed mice

Abstract: Salecan is a recently identified water-soluble viscous extracellular b-1,3-D-glucan polysaccharide from an Agrobacterium species. It is a high-molecular-mass polymer (about 2 £ 10 6 Da) and composed of a linear chain of glucosyl residues linked through a repeat unit of seven b-(1,3) and two a-(1,3) glucosidic bonds. In the present study, we examined the effects of dietary Salecan fed at 2 and 5 % in a high-fat diet (64 % energy) in C57BL/6J mice. After 6 weeks, mice fed 2 and 5 % Salecan had significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…These properties suggested that Salecan could be utilized in the food industry as a new source of thickening agent and medical industry for preventing and treating constipation. [29][30][31][32][33][34] In addition, Salecan affords a high density of hydroxyl groups, which can be modied to provide greater exibility in the preparation of hydrogels. Recently, Salecan-based hydrogels were successfully fabricated in our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…These properties suggested that Salecan could be utilized in the food industry as a new source of thickening agent and medical industry for preventing and treating constipation. [29][30][31][32][33][34] In addition, Salecan affords a high density of hydroxyl groups, which can be modied to provide greater exibility in the preparation of hydrogels. Recently, Salecan-based hydrogels were successfully fabricated in our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of salecan is a linear (1→3)-␤-d-glucan consisted of ␤-1-3-linked glucopyranosyls with a small quantity of ␣-1-3-linked [33]. As a novel polysaccharide, salecan has been utilized in the fields of both food and medical in our laboratory [34][35][36][37][38]. With a high density of hydroxyl groups, the large molecular weighted (2 × 10 6 Da) salecan could be further modified for multifarious applications.…”
Section: Introductionmentioning
confidence: 99%
“…The method of beta‐glucan preparation was previously described (Zhang et al, ). Briefly, Agrobacterium sp.…”
Section: Methodsmentioning
confidence: 99%